2018
DOI: 10.1097/md.0000000000012191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rational emotive behavior therapy on stress management and irrational beliefs of special education teachers in Nigerian elementary schools

Abstract: Background/Objective:From a rational emotive behavior therapy viewpoint, stress-related disorders originate from irrational beliefs and self-defeating philosophies and attitude. Individuals affected by stress are different from those ones with neurotic problems mainly because the stressed individuals have irrational beliefs about specific, short-term, or more readily identifiable events, in contrast to the more mundane and diffuse difficulties faced by neurotic persons. The present study aimed to examine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 35 publications
6
73
0
2
Order By: Relevance
“…Therefore, the findings of the present study support existing literature which has shown that REBT-informed interventions offer coping strategies and enables adolescents and youths to cope and manage symptoms of burnout. [ 49 , 50 , 52 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the findings of the present study support existing literature which has shown that REBT-informed interventions offer coping strategies and enables adolescents and youths to cope and manage symptoms of burnout. [ 49 , 50 , 52 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 49 ] The procedure adopted for assigning athletes to the groups was as described in past interventions. [ 50 , 51 ] After assignment to groups, the 12-week intervention program followed. After the 12th week, the Athlete Burnout Questionnaire was administered to collect post-test data.…”
Section: Methodsmentioning
confidence: 99%
“…The random allocation sequence used to assign students to the groups was generated by a Random Allocation Software. [22] The procedure adopted for assigning students to the groups was as described in Onuigbo et al [16] To minimize bias, data analysts were blinded as some portions of the data collection instrument was blurred.…”
Section: Measurementioning
confidence: 99%
“…Rational emotive therapy menekankan bahwa manusia berfikir, beremosi dan bertindak secara simultan (Corey, 2013). Rational emotive therapy mampu menurunkan tingkat stres dan keyakinan irasional yang bergeser kearah yang lebih rasional (Onuigbo et al, 2018). Subjek pada kasus ini mengalami permasalahan menghadapi hubungan sosial, adanya pemikiran/keyakinan irasional untuk menganggap dirinya tidak diterima dilingkungan sosial, ketakutan kehilangan teman dekat karena berpikir hanya memiliki satu teman dekat, ketakutan saat teman dekat dengan orang lain, takut ditinggal dan kesepian.…”
Section: Latar Belakangunclassified
“…RET berfungsi dengan baik untuk menurunkan stres pada individu selama menjalani kegiatan sehari-hari, hal ini sesuai dengan penelitian yang dilakukan oleh (Onuigbo et al, 2018) bahwa RET dapat menurunkan tingkat stres dan keyakinan irasional individu bergeser menjadi kayakinan rasional. RET juga dapat menurunkan tingkat gejala-gejala depresi seperti yang dialami Subjek (merubah suasana hati, pola tidur, prduktifitas) hal ini sesuai dengan penelitian (Zhaleh, Zarbakhsh, & Faramarzi, 2014) yang menyatakan bahwa REBT dapat menurunkan gejala-gejala depresi pada diri individu.…”
Section: Pembahasanunclassified